2011
DOI: 10.1080/15222055.2010.549030
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Partial Replacement of Fish Meal Protein by Microalgae on Growth, Feed Intake, and Body Composition of Atlantic Cod

Abstract: A feeding trial was conducted with juvenile Atlantic cod Gadus morhua (initial mean weight, 40.7 g) in which a combination of dried Nannochloropsis sp. and Isochrysis sp. replaced fish meal protein in isonitrogenous, isocaloric diets. Three experimental diets (55% protein, 16.5% fat; calculated gross energy = 5,328 kcal/kg) were formulated to replace 0, 15, or 30% of dietary fish meal protein. At the conclusion of the 84‐d study, no differences in survival, feed conversion ratios, viscerosomatic indices, and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(23 citation statements)
references
References 43 publications
1
22
0
Order By: Relevance
“…and Isochrysis sp. up to 11.9% reduced the feed intake and growth performance of Atlantic cod ( 81 ) and Schizochytrium limacinum and N. oceanica supplementation up to 17% reduced rainbow trout growth performance ( 82 ). The negative impact of microalgae blends was suggested to be due to their low palatability ( 81 ).…”
Section: Discussionmentioning
confidence: 99%
“…and Isochrysis sp. up to 11.9% reduced the feed intake and growth performance of Atlantic cod ( 81 ) and Schizochytrium limacinum and N. oceanica supplementation up to 17% reduced rainbow trout growth performance ( 82 ). The negative impact of microalgae blends was suggested to be due to their low palatability ( 81 ).…”
Section: Discussionmentioning
confidence: 99%
“…and Isochrysis sp. decreased the feed intake and growth performance, which may be due to the negative effect on the palatability of diet [ 19 ]. Generally, the carbohydrate content in chlorella is about 12-17% with the forms of starch, cellulose, and other polysaccharides [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…The negative effects of 33.0%, 66.0%, and 100.0% biofloc diets compared to the control diet might be owing to palatability problems (Walker and Berlinsky, 2011) in addition to imbalances in diet components. On the other hand, several studies indicated higher feed intake, feed efficiency, and growth performance due to biofloc feeding (Mahanand et al, 2013;Shyne et al, 2014).…”
Section: Advances Inmentioning
confidence: 99%